HEMŞİRE VE HASTA BAKICILARDA HEPATİT A İNFEKSİYONU RİSK FAKTÖRLERİ - BAŞARAN, Gürkan; BÜYÜKBEŞE, Mehmet Akif; ÖZTÜRK, Recep (Cerrahpaşa Medical Journal, 2014)
Background and Design. The availability of active immunization against hepatitis A infection inspired many investigators to evaluate the necessity for vaccination of health care workers; and contradicting recommendations are being made on this issue. Numerous studies exist showing that seroprevalence of hepatitis A is similar between health care workers and general population. However some risk factors are reported to exist among health care workers. In order to determine the presence of risk factors of hepatitis A that necessitate vaccination we assessed the immune status and some variables in 115 health care workers in Cerrahpaşa Medical School. Results. Of the 115 workers 32 (28%) were men and 83 (72%) were women. Sixtynine (60%) were nurses and 46 (40%) were office workers. Sixty of them (52%) were working in medical departments while 55 (48%) were working in surgical departments. The mean duration of employment was 11.2 years. The mean age of the workers was 33.3 years. AntiHAV was positive in 104 workers (90.4%). Seropositivity ratios were statistically similar between seropositive and seronegative workers in terms of age, sex, occupation, duration and department of employment. Conclusion. As a result we have not found any risk factors for hepatitis A in nurses and the office workers in our hospital which indicate necessity for vaccination.